Colonial jewelry from 16th and 17th-century nueva granada: general considerations and pictorial documents. (2013)
Not much is known about Colombian colonial jewelry.With this study we want to do a small contribution tothat knowledge. Our sources information were essentiallypictorial documents of the sixteenth and seventeenth.Through them, we can see how were imposed Europeanfashions of the time, but without forgetting the indigenoussurvivals. The development of New Granada jewelrywas very influenced by their own materials: gold, silver,pearls and emeralds. Unfortunately, we know the namesof several jewelers and lapidaries, but we can not knowwhat works executed, because no marks or documentswe have allowed.